2021
DOI: 10.3389/fmicb.2021.719360
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and SSU rDNA-Based Phylogeny of Two Heterotrich Ciliates (Ciliophora, Heterotrichea) Collected From Subtropical Wetlands of China, Including the Description of a New Species, Linostomella pseudovorticella n. sp.

Abstract: The Heterotrichea Stein, 1859 are a group of ciliated protists (single-celled eukaryotes) that occur in a wide variety of aquatic habitat where they play important roles in the flow of nutrients and energy within the microbial food web. Many species are model organisms for research in cytology and regenerative biology. In the present study, the morphology and phylogeny of two heterotrich ciliates, namely, Linostomella pseudovorticella n. sp. and Peritromus kahli Villeneuve-Brachon, 1940, collected from subtrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Through this comprehensive examination, the results are summarized as follow: (1) a total of 30 valid species were recognized, four of which are new (Fig. 3 (Foissner 2016;Foissner et al 2002); (4) three nominal Condylostoma species, C. stagnale, C. vastum, and C. vorticella, have been or should be transferred to Linostomella (Chi et al 2020b;Jin et al 2021).…”
Section: Identification Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this comprehensive examination, the results are summarized as follow: (1) a total of 30 valid species were recognized, four of which are new (Fig. 3 (Foissner 2016;Foissner et al 2002); (4) three nominal Condylostoma species, C. stagnale, C. vastum, and C. vorticella, have been or should be transferred to Linostomella (Chi et al 2020b;Jin et al 2021).…”
Section: Identification Characteristicsmentioning
confidence: 99%
“…The family Condylostomatidae is a relatively well-studied family within the Heterotrichea, and several studies on the diversity of its five genera, Chattonidium Villeneuve-Brachon, 1937, Condylostentor Jankowski, 1978, Condylostoma Bory de Saint-Vincent, 1824, Condylostomides da Silva Neto, 1994, and Linostomella Aescht in Foissner et al, 1999, have been reported in recent years (Chen et al 2007;Chi et al 2020b;Fernandes et al 2015;Jin et al 2021;Kim et al 2012;Modeo et al 2006;Shao et al 2006;Yan et al 2015). The type genus, Condylostoma, is the most speciose of these genera and is commonly found in brackish or marine habitats.…”
Section: Introductionmentioning
confidence: 99%